Gogol's topos in the visions of Ukrainian writers (based on the works of Yu. Yanovskyi, O. Zvychaina, V. Mynk, Y. Scherbak) (Literatures of the World: Poetics, Mentality and Spirituality, 2015)
The article analyzes the interpretation peculiarities of Gogol's topoi by the Ukrainian writers of the second half of the ХXth century. The semantic dominants of imitation and assimilation of Gogol's picture of the world are defined. Literary versions of Gogol's text are analyzed according to the  context in which they were created. It is determined that Gogol's topoi are significant for Ukrainian literature due to their informational content.
Keywords: topos; Gogol's text; art space; provincial text